Conceptual Design of a Liquid Helium Vertical Test-Stand for 2m long Superconducting Undulator Coils. Issue 1 (1st December 2022) - Marchetti, B.; Abeghyan, S.; Baader, J.; Barbanotti, S.; Casalbuoni, S.; Di Felice, M.; Eckoldt, H.-J.; Englisch, U.; Grattoni, V.; Grau, A.; Hauberg, A.; Jensch, K.; et al.
Abstract: Superconducting Undulators (SCUs) can produce higher photon flux and cover a wider photon energy range compared to permanent magnet undulators (PMUs) with the same vacuum gap and period length. To build the know-how to implement superconducting undulators for future upgrades of the European XFEL facility, the test stand SUNDAE1 for the characterization of SCU is being developed. The purpose of SUNDAE1 is the training, tuning and development of new SCU coils by means of precise magnetic field measurements. The experimental setup will allow the characterization of magnets up to 2m in length. These magnets will be immersed in a Helium bath at 4K or 2K temperature. In this article, we describe the experimental setup and highlight its expected performances.